RELEVANSI NILAI-NILAI PANCASILA DALAM MENGHADAPI TANTANGAN GLOBALISASI - Junaedi, Oding (LEX OMNIBUS : Jurnal Hukum Tata Negara dan Administrasi Negara, 2024)
Globalization brings various challenges to the sustainability of Pancasila values ​​in national and state life. This study aims to analyze the relevance of Pancasila values ​​in facing the challenges of globalization and obstacles in its implementation using normative legal research methods. This study focuses on the study of laws and regulations and legal doctrines related to the implementation of Pancasila values ​​in the national legal system. The results of the study indicate that although Pancasila remains relevant as a guideline in maintaining national identity, its implementation faces various obstacles. The main challenges faced include the influence of foreign cultures that can shift local values, the decline in the understanding of the younger generation towards the nation's ideology, and the increase in social and economic inequality. To overcome these challenges, it is necessary to strengthen regulations that accommodate Pancasila values ​​in national policies, improve Pancasila-based education, and the role of the state in reducing socio-economic disparities. With these steps, Pancasila can continue to be the main foundation in building a sovereign and just nation in the global era.